The Problem of Morality in Soft and Hard Legal Positivism - Ataollah Salehi; Mahdi Balavi (Journal of Philosophical Investigations, 2023)
The law is the reason and guide for human behavior; therefore, it is a normative social practice. But what conditions should a norm have to be called a law and what is its relationship with morality? Is the criterion of being a law, its origin or its content? In response, the school of natural law and legal positivism are two long-standing competing theories. The school of natural law, which is a recommendatory and prescriptive, emphasizes the content, but the positivism, which is descriptive and explanatory, emphasizes the source of the law. Of course, at first, the school of natural law looked for content in religion, but today, individual human rights as the subject and social contract as the process has noticed. The conceptual space of legal positivism is formed by the combination of two theses of social reality and separability, and the separation theory denies any conceptual and content relationship between law and morality. but, Dworkin, by criticizing the separation theory, divided positivism into two opposing camps, soft and hard, and the soft positivism abandoned the separation theory to some extent. But is soft legal positivism compatible with the claim of the authority of the law and its guiding function? Is discovered or invented morality an essential and existential part of the law or is it a criterion for its evaluation? In this article, the mentioned questions are analyzed in order to discover the position of hard and soft legal positivism.